Bronchial hyperresponsiveness in lung transplant recipients: lack of correlation with airway inflammation. Issue 6 (June 1997) - Liakakos, P; Snell, G I; Ward, C; Johns, D P; Bamford, T L; Williams, T J; Walters, E H
Abstract : BACKGROUND: Bronchial hyperresponsiveness (BHR) to methacholine has been reported to occur in most lung transplant recipients. BHR to physical stimuli such as exercise and non-isotonic aerosols has not been as extensively studied in this subject population. This report aims to assess the presence and degree of BHR to methacholine and hypertonic saline in stable lung transplant recipients and to relate it to the presence of airway inflammation. METHODS: Ten patients undergoing bilateral sequential lung transplantation and six heart-lung transplant recipients, all with stable lung function, were recruited 66-1167 days following transplantation. Subjects underwent a methacholine challenge and bronchoscopy for sampling of bronchoalveolar lavage fluid, transbronchial and endobronchial biopsy tissues. Hypertonic saline challenge was performed six days later. RESULTS: Nine of the 16 transplant recipients had positive methacholine challenges (geometric mean PD20 0.18 mg, interquartile range 0.058-0.509) and three of these subjects also had positive hypertonic saline challenges (PD15 = 2.3, 33.0, and 51.5 ml). No clear relationship was found between BHR to either methacholine or hypertonic saline and levels of mast cells, eosinophils or lymphocytes in samples of biopsy tissue or lavage fluid. CONCLUSIONS: Most of the lung transplant recipients studied were responsive to methacholine and unresponsive to hypertonic saline. BHR was not clearly related to airway inflammation, suggesting an alternative mechanism for BHR following lung transplantation from that usually assumed in asthma.